Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Our platform provides a seamless experience for finding precise answers from a network of experienced professionals. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

4
To eliminate the y terms from the following system of equations, the first
equation must be multiplied by 5 and the second equation must be
multiplied by 4.
x - 4y = 11
-3x + 5y = 25ها
If the statement is true, type true in the space provided, if it is false, replace the underline words with the words that will make the statement true.


Sagot :

Answer:

True

Step-by-step explanation:

x - 4y = 11 → (1)

- 3x + 5y = 25 → (2)

Multiply (1) by 5 and (2) by 4 to eliminate the y- term

5x - 20 y = 55 → (3)

- 12x + 20y = 100 → (4)

Add (3) and (4) term by term to eliminate y

- 7x + 0 = 155

- 7x = 155 ← y- term is eliminated